Pneumococcal epidemiology among us adults hospitalized for community-acquired pneumonia. Issue 25 (31st May 2019) - Isturiz, Raul E.; Ramirez, Julio; Self, Wesley H.; Grijalva, Carlos G.; Counselman, Francis L.; Volturo, Gregory; Ostrosky-Zeichner, Luis; Peyrani, Paula; Wunderink, Richard G.; Sherwin, Robert; Overcash, J. Scott; Oliva, Senen Pena; et al.
Abstract: Background: Few studies have measured the burden of adult pneumococcal disease after the introduction of 13-valent pneumococcal conjugate vaccine (PCV13) into the US infant vaccination schedule. Further, most data regarding pneumococcal serotypes are derived from invasive pneumococcal disease (IPD), which represents only a fraction of all adult pneumococcal disease burden. Understanding which pneumococcal serotypes cause pneumonia in adults is critical for informing current immunization policy. The objective of this study was to measure the proportion of radiographically-confirmed (CXR+) community-acquired pneumonia (CAP) caused by PCV13 serotypes in hospitalized US adults. Methods: This observational, prospective surveillance study recruited hospitalized adults aged ≥18 years from 21 acute care hospitals across 10 geographically-dispersed cities in the United States between October 2013 and September 2016. Clinical and demographic data were collected during hospitalization. Vital status was ascertained 30 days after enrollment. Pneumococcal serotypes were detected via culture from the respiratory tract and normally-sterile sites (including blood and pleural fluid). Additionally, a novel, Luminex-based serotype-specific urinary antigen detection (UAD) assay was used to detect serotypes included in PCV13. Results: Of 15, 572 enrolled participants, 12, 055 eligible patients with CXR+CAP were included in the final analysis population. Mean age was 64.1 years and 52.7% were aged ≥65 years. Common comorbidities included chronic obstructive pulmonary disease (43.0%) and diabetes mellitus (28.6%). PCV13 serotypes were detected in 552/12, 055 (4.6%) of all patients and 265/6347 (4.2%) of those aged ≥65 years. Among patients aged 18–64 years PCV13 serotypes were detected in 3.8–5.3% of patients depending on their risk status. Conclusions: After implementation of a pneumococcal conjugate vaccination program in US children, and despite the herd protection observed in US adults, a persistent burden of PCV13-type CAP remains in this population.